Research on professional responsibility and ethics in accounting. Vol 24 - Baker, C. Richard (Emerald Publishing Limited, 2021)
This edition of Research on Professional Responsibility and Ethics in Accounting includes articles from a distinguished group of authors. The topics covered explore many aspects of professional responsibility and ethics in accounting, including Giving Voice to Values, Whistleblowing, Earnings Management, and Materiality.
Includes index.
Keywords: Accounting -- Moral and ethical aspects.; Accountants -- Professional ethics.; Business & Economics -- Accounting -- General.; Accounting.; elektronické knihy; electronic books